2011
DOI: 10.1089/jwh.2010.2328
|View full text |Cite
|
Sign up to set email alerts
|

Substance Abuse, Violence, and HIV in Women: A Literature Review of the Syndemic

Abstract: Women in the United States are increasingly affected by HIV/AIDS. The SAVA syndemic-synergistic epidemics of substance abuse, violence, and HIV/AIDS-is highly prevalent among impoverished urban women and potentially associated with poor HIV outcomes. A review of the existing literature found 45 articles that examine SAVA's impact on (1) HIV-associated risk-taking behaviors, (2) mental health, (3) healthcare utilization and medication adherence, and (4) the bidirectional relationship between violence and HIV st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
268
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(289 citation statements)
references
References 71 publications
(84 reference statements)
18
268
1
2
Order By: Relevance
“…Finally, while cigarette smoking was associated with unprotected sex among both genders, sex under the influence of alcohol or drugs, and having suffered any verbal violence were independent correlates of unprotected sex among women only, and this result was consistent with other studies 26,27,28,29,30,31 . Sex under the influence of alcohol or drugs can alter cognitive abilities and decision-making power, thus potentially leading to high risk behaviors 6 .…”
Section: Discussionsupporting
confidence: 90%
“…Finally, while cigarette smoking was associated with unprotected sex among both genders, sex under the influence of alcohol or drugs, and having suffered any verbal violence were independent correlates of unprotected sex among women only, and this result was consistent with other studies 26,27,28,29,30,31 . Sex under the influence of alcohol or drugs can alter cognitive abilities and decision-making power, thus potentially leading to high risk behaviors 6 .…”
Section: Discussionsupporting
confidence: 90%
“…The presence of structural factors and alcohol and drug consumption often interweaves in these relations, producing conflicts and further favoring men's control over women, including by violent means. A literature review on the intersection between substance abuse, violence, and HIV/AIDS in women in the United States found that 76% of women that report physical assault and rape in adulthood were victims of their own intimate partners 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of the literature revealed several mechanisms that link these women's health problems and empirical data have supported these associations. [5][6][7][8] Women who are forced to have sex with an HIV-positive partner could be exposed to infection, and living with violence or the fear of abuse by an intimate partner can limit women's ability to negotiate safe sex behaviors. [9][10][11][12][13][14][15][16] Conversely, women who are HIV-positive might experience abuse upon disclosure of their HIV status.…”
Section: Introductionmentioning
confidence: 99%